2012
DOI: 10.1177/1091581812445476
|View full text |Cite
|
Sign up to set email alerts
|

Kolaviron Biflavanoids of Garcinia Kola Seeds Protect Atrazine-Induced Cytotoxicity in Primary Cultures of Rat Leydig Cells

Abstract: We sought to explore the mechanism by which kolaviron (Kol) protects against atrazine (ATZ)-induced toxicity of cultured interstitial Leydig cells (ILCs). In our experiments, treatment with Kol improved Leydig cell viability and significantly reduced malondialdehyde (MDA) and reactive oxygen species (ROS) levels. Further investigations revealed a reduction in glutathione peroxidase (GSH-Px), glutathione reductase (GR), glutathione-S-transferase (GST) and elevation of superoxide dismutase 1 (SOD-1) and superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 24 publications
5
24
0
Order By: Relevance
“…It was found that kolaviron normalized the expression level of CYP11A1 that was previously increased 3-fold of control by a chemical toxicant atrazine in rat interstitial Leydig cells. 144 A similar effect was observed for quercetin. 146 …”
Section: Polyphenols-mediated Modulation Of Cyp Gene Expressionsupporting
confidence: 71%
See 1 more Smart Citation
“…It was found that kolaviron normalized the expression level of CYP11A1 that was previously increased 3-fold of control by a chemical toxicant atrazine in rat interstitial Leydig cells. 144 A similar effect was observed for quercetin. 146 …”
Section: Polyphenols-mediated Modulation Of Cyp Gene Expressionsupporting
confidence: 71%
“…143 Biflavanone kolaviron was shown to suppress the expression of CYP11A1. 144 This isoform initiates steroidogenesis by converting cholesterol to pregnenolone on the inner mitochondrial membrane. 145 Kolaviron is contained in the seeds of Garcinia kola, a flowering plant traditionally used in Africa as a medicine against throat infections and chest cold.…”
Section: Polyphenols-mediated Modulation Of Cyp Gene Expressionmentioning
confidence: 99%
“…The most likely explanation for an increase in DMC1 foci is inefficient DNA repair under toxic conditions. Specifically, previous studies have shown that exposure to ATZ induces oxidative stress in exposed cells, which is characterized by the increased activity of the cytochrome C system and detoxifying glutathione S-transferases 43, 44 . Oxidative stress increases the concentration of oxidizing molecules known as reactive oxygen species (ROS).…”
Section: Discussionmentioning
confidence: 99%
“…This supports our present findings and indicates that RUT could enhance the antioxidative capacity of GSH and GSH‐Px in our experimental model. Consequently, the increased GSH and GSH‐Px activities in these animals were considered adaptive and not adverse (Martin et al., ) and were associated with the ability of flavonoids to increase the mRNA expression of antioxidant genes (Abarikwu, Farombi, & Pant, ).…”
Section: Discussionmentioning
confidence: 99%